Cultivating string quartets in Beethoven's Vienna - November, Nancy ca. 20./21. Jh (Boydell & Brewer, 2017)
This book is the first detailed contextual study of string quartets in Beethoven's Vienna, at a time when that genre reigned supreme among the different chamber genres. Focusing on a key transition period in the early nineteenth century, which bore witness to fundamental shifts in the 'private' sphere of music-making, it explores the 'cultivation' of string quartets by composers, critics, listeners, performers, publishers and patrons. The book highlights these parties' interactions, ideas and ideals, which were central to defining the unique cultures of chamber music arising at this time. We gain fresh insights into publishing and marketing, performance venues and practices, review culture, listening theories and practices, and composition in early nineteenth-century Vienna. Until now, the unique theatricality of chamber music, and the 'social' nature of its discourse, has been poorly appreciated. Cultivating String Quartets in Beethoven's Vienna addresses this misconception and enriches our understanding of this crucial period of change, in which concert life began and previously 'private' music was moved out onto the stage. NANCY NOVEMBER is Associate Professor in Musicology at the University of Auckland